THE IMPACT OF RELIANCE JIO ON DIGITAL INDIA INITIATIVE - Sheeba, Gopika; P.S, Krishnapriya; J Menon, Rashmi (International Journal of Psychosocial Rehabilitation, 2020)
The Digital India Initiative, introduced by the Ministry of Electronics and Information Technology of the Government of India, ensures that government services are made available to citizens electronically. It aims to improve the online infrastructure and increase the internet connectivity in rural areas. The telecommunications market had seen a tremendous change after the emergence of Reliance Jio. It provided free calling, free data with the 4G network, and promoted digital services. Jio promises to bridge the rural-urban digital divide. The purpose of this study is to examine the impact of Reliance Jio on digital India. The primary data was used for the study and collected using a structured questionnaire. The study also analyzes the market potential of Reliance Jio.